2020
DOI: 10.3390/molecules25163716
|View full text |Cite
|
Sign up to set email alerts
|

Baking Optimization as a Strategy to Extend Shelf-Life through the Enhanced Quality and Bioactive Properties of Pulse-Based Snacks

Abstract: Food processing optimization can enhance the nutrient bioavailability, storage time, and stability of convenience foods. Baking is a heat and mass transfer process with a high impact on the shelf-life of the obtained product; a small variation in the parameters during baking can lead to significant changes in the end baked product, as it significantly affects the food nutrient profile and bioactive compounds. Response surface methodology (RSM) was used for mapping a response surface over a particular region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Altering processing conditions such as baking temperature and time to assess their influence on the gluten-free system is a sustainable, easy and cost-effective strategy (Rodríguez et al, 2022). Baking generates myriad chemical reactions and texture changes that can alter the final product's quality and taste (Rico et al, 2020). Multiple studies (Bredariol et al, 2020; NFS 54,1 Chakraborty et al, 2020) have suggested that varying baking conditions can impact the moistness, hardness and volume of baked gluten-free products.…”
Section: Introductionmentioning
confidence: 99%
“…Altering processing conditions such as baking temperature and time to assess their influence on the gluten-free system is a sustainable, easy and cost-effective strategy (Rodríguez et al, 2022). Baking generates myriad chemical reactions and texture changes that can alter the final product's quality and taste (Rico et al, 2020). Multiple studies (Bredariol et al, 2020; NFS 54,1 Chakraborty et al, 2020) have suggested that varying baking conditions can impact the moistness, hardness and volume of baked gluten-free products.…”
Section: Introductionmentioning
confidence: 99%
“…Baking is an alternative technology to manufacture lower oil snacks. Nevertheless, compared with fried process, the baking corn snacks are less crispy than the fried ones (Colla et al, 2018;Rico et al, 2020). In order to satisfy the need of desirable texture and taste, formula should be changed (Jiang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%